Anxiety in Children and Adolescents with Chronic Kidney Disease - Multicenter National Study Results - Katarzyna Kiliś-Pstrusińska; Anna Medyńska; Piotr Adamczak; Irena Bałasz- Chmielewska; Ryszard Grenda; Agnieszka Kluska-Jóźwiak; Beata Leszczyńska; Ilona Olszak-Szot; Monika Miklaszewska; Maria Szczepańska; Marcin Tkaczyk; Anna Wasilewska; et al. (Karger Publishers, 2013)
Background/Aims: Chronic medical illness is a significant risk factor for the development of psychiatric disorders. The aims of the study were: to investigate the level of anxiety in children with chronic kidney disease (CKD) and to identify factors associated with the presence of that emotional problem. Methods: CKD children on hemodialysis (HD, n=22), peritoneal dialysis (PD, n=20,) and on conservative treatment (CT, n=95) were enrolled in the study. We used State-Trait Anxiety Inventory (STAI) for adolescents and STAI-C for children. Socio-demographic and physical factors were assessed. Results: There was a significantly higher level of anxiety-state among HD children (8-12 years) compared with other groups of participants of the same age and Polish population norms. The level of anxiety among adolescents (13-18 years), both anxiety-state and anxiety-trait, was significantly higher in the HD group compared with other groups, which did not differ among themselves. In the HD adolescents, there was a correlation between the anxiety-state and the duration of the disease as well as with the number of hospitalizations. PD adolescents in the mainstream education had higher levels of anxiety-state and anxiety-trait compared with home schooled patients. Conclusions: Even though children and adolescents with CKD are at risk of developing a variety of emotional disorders, the level of anxiety among the researched group, with the exception of HD patients, was not significantly different than the level of anxiety among healthy subjects. Adolescents on HD who present a high level of anxiety should undergo long-term psychological treatment.